Beyond the classroom: How OCB, self-efficacy, and remuneration shape teacher loyalty in non-formal education - Bahri, Efri Syamsul; Novianti, Sindi; Rochman, Muhammad Mughni Izzatur; Pratiwi, Redna; Tohani, Entoh; Joronavalona, Rasamimanana (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
This study examines the impact of organisational citizenship behaviour (OCB), self-efficacy, and compensation on teacher loyalty within the context of non-formal education in Indonesia. Employing a quantitative research design with a descriptive approach, data were collected from non-formal education teachers working at Learning Activity Studios (Sanggar Kegiatan Belajar, or SKB) across Indonesia. Structural Equation Modelling with Partial Least Squares (SEM-PLS) was used for data analysis, processed through SmartPLS software. The findings reveal that both OCB and remuneration have a statistically significant positive effect on teacher loyalty. Additionally, self-efficacy also positively contributes to teacher loyalty, although to a lesser extent. These results highlight the critical role of internal psychological and organisational factors in fostering commitment among non-formal education teachers. It is recommended that SKB managers enhance supportive work environments that promote citizenship behaviour and self-efficacy. Furthermore, government policies should reinforce fair and sustainable remuneration systems to strengthen teacher loyalty and ensure the continued quality of non-formal education services in Indonesia.